RNA is taking its Toll: Impact of RNA‐specific Toll‐like receptors on health and disease. Issue 2 (17th December 2018) - Vierbuchen, Tim; Stein, Karina; Heine, Holger
Abstract: RNA‐sensing Toll‐like receptors (TLRs) are often described as antiviral receptors of the innate immune system. However, the past decade has shown that the function and relevance of these receptors are far more complex. They were found to be essential for the detection of various bacterial, archaeal, and eukaryotic microorganisms and facilitate the discrimination between dead and living microbes. The cytokine and interferon response profile that is triggered has the potential to improve the efficacy of next‐generation vaccines and may prevent the development of asthma and allergy. Nevertheless, the ability to recognize foreign RNA comes with a cost as also damaged host cells can release nucleic acids that might induce an inappropriate immune response. Thus, it is not surprising that RNA‐sensing TLRs play a key role in various autoimmune diseases. However, promising new inhibitors and antagonists are on the horizon to improve their treatment.